Використання штучного інтелекту для створення ігрового контенту - Олещенко, В. Б.; Рижкова, Є. М.; Козловець, С. О. (ХНУРЕ, 2023)
During the work, a game level was created using Unity. Stable diffusion AI was used to generate materials to be futher used in the game level. The use of neural networks in the development of video games was evaluated.
Keywords: розробка ігор; ігровий контент